High resolution imaging of acne lesion development and scarring in human facial skin using OCT-based microangiography - Baran, Utku (Lasers Surg Med, 2015)
BACKGROUND AND OBJECTIVE: Acne is a common skin disease that often leads to scarring. Collagen and other tissue damage from the inflammation of acne give rise to permanent skin texture and microvascular changes. In this study, we demonstrate the capabilities of optical coherence tomography based microangiography in detecting high-resolution, three-dimensional structural and microvascular features of in vivo human facial skin during acne lesion initiation and scar development. MATERIALS AND METHODS: A real time swept source optical coherence tomography system is used in this study to acquire volumetric images of human skin. The system operates on a central wavelength of 1310 nm with an A-line rate of 100 kHz, and with an extended imaging range (~12 mm in air). The system uses a handheld imaging probe to image acne lesion on a facial skin of a volunteer. We utilize optical microangiography (OMAG) technique to evaluate the changes in microvasculature and tissue structure. RESULTS: Thanks to the high sensitivity of OMAG, we are able to image microvasculature up to capillary level and visualize the remodeled vessels around the acne lesion. Moreover, vascular density change derived from OMAG measurement is provided as an alternative biomarker for the assessment of human skin diseases. In contrast to other techniques like histology or microscopy, our technique made it possible to image 3D tissue structure and microvasculature up to 1.5 mm depth in vivo without the need of exogenous contrast agents. CONCLUSION: The presented results are promising to facilitate clinical trials aiming to treat acne lesion scarring, as well as other prevalent skin diseases, by detecting cutaneous blood flow and structural changes within human skin in vivo.